The effect of 8-day oral taurine supplementation on thermoregulation during low-intensity exercise at fixed heat production in hot conditions of incremental humidity - Jenny Peel (European Journal of Applied Physiology, 2024)
Purpose: To determine the effect of taurine supplementation on sweating and core temperature responses, including the transition from compensable to uncompensable heat stress, during prolonged low-intensity exercise of a fixed-heat production (~200W/m2) in hot conditions (37.5°C), at both fixed and incremental vapour-pressure. Methods: Fifteen females (n=3) and males (n=12; 27±5years, 78±9kg, ̇O2max 50.3±7.8mL/kg/min), completed a treadmill walking protocol (~200W/m2 heat production [Ḣprod]) in the heat (37.5±0.1°C) at fixed- (16mmHg) and ramped-humidity (Δ1.5mmHg/5-min) following one week of oral taurine supplementation (50mg/kg/bm) or placebo, in a double-blind, randomised, cross-over design. Participants were assessed for whole-body sweat loss (WBSL), local sweat rate (LSR), sweat gland activation (SGA), core temperature (Tcore), breakpoint of compensability (Pcrit) and calorimetric heat transfer components. Plasma volume and plasma taurine concentrations were established through pre- and post-trial blood samples. Results: Taurine supplementation increased WBSL by 26.6% and 5.1% (p=0.035), LSR by 15.5% and 7.8% (p=0.013), SGA (1x1cm) by 32.2% and 29.9% (p<0.001) and SGA (3x3cm) by 22.1% and 17.1% (p=0.015) during the fixed- and ramped-humidity exercise periods, respectively. Evaporative heat loss was enhanced by 27% (p=0.010), heat-storage reduced by 72% (p=0.024) and Pcrit was greater in taurine vs placebo (25.0mmHg vs 21.7mmHg; p=0.002). Conclusion: Taurine supplementation increased sweating responses during fixed Ḣprod in hot conditions, prior to substantial heat strain and before the breakpoint of compensability, demonstrating improved thermoregulatory capacity. The enhanced evaporative cooling and reduced heat-storage delayed the subsequent upward inflection in Tcore –represented by a greater Pcrit– and offers a potential dietary supplementation strategy to support thermoregulation.